Properties of fibreboard (FBs) and recycle fibreboard (rFBs) and analysis of their wastage after recycling. Issue 1 (September 2020) - Nuryawan, A; Risnasari, I; Pohan, A P; Husna, A U; Nasution, T I; Banurea, R; Hartini, K S
Abstract: Fibreboards (FBs) bonded by urea-formaldehyde (UF) resin derived from industry were intended to undergo cyclist test, a simulation of recycling activity. Objective of this study was to compare quality of FBs before and after recycling including analyse its wastage. Methods of this study were consisted of evaluation physical and mechanical properties of FBs before recycling, cyclist test, remanufacturing FBs, evaluation recycle FBs (rFBs), comparing the properties between FBs and rFBs and analysing the wastage of recycling activity both solid residue and liquid disposal. Results of this study showed physical and mechanical properties of FBs changed after recycling presumably because of the difference in reproduction method. Some physical properties showed better quality, while the mechanical properties performed decrease drastically. Cyclist test predicted that FBs were more resistant in 3 (three) cyclist compared to that of rFBs. There was wastage of recycling consisting of macro solid fibre with length dimension of 1000.51±339.21 μm and micro solid fibre with variation in distribution size. Liquid disposal (LD) contained nitrogen (N) with amount 0.05% presumably from sol fraction of UF resin. These findings suggested that remanufacturing of rFBs was feasible even though wastage of recycling activity was inevitable. Fortunately, LD can be utilized further for example for fertilizer because the N content exists.